2020
DOI: 10.3389/fcell.2020.584513
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential Channels as an Emerging Target for the Treatment of Parkinson’s Disease: An Insight Into Role of Pharmacological Interventions

Abstract: Parkinson’s disease (PD) is a neurodegenerative disorder characterized by the symptoms of motor deficits and cognitive decline. There are a number of therapeutics available for the treatment of PD, but most of them suffer from serious side effects such as bradykinesia, dyskinesia and on-off effect. Therefore, despite the availability of these pharmacological agents, PD patients continue to have an inferior quality of life. This has warranted a need to look for alternate strategies and molecular targets. Recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 105 publications
(122 reference statements)
0
15
0
Order By: Relevance
“…Considering that the changes in the calcium homeostasis and oxidative stress are associated with the degeneration of dopaminergic neurons in substantia nigra, it has been suggested that TRP channels could mediate some of the mechanisms that lead to the development of the PD [ 53 ]. It has been reported that TRPV1 activation triggers Ca 2+ -dependent cell death [ 54 ] and NADPH-oxidase-mediated ROS production in microglia [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the changes in the calcium homeostasis and oxidative stress are associated with the degeneration of dopaminergic neurons in substantia nigra, it has been suggested that TRP channels could mediate some of the mechanisms that lead to the development of the PD [ 53 ]. It has been reported that TRPV1 activation triggers Ca 2+ -dependent cell death [ 54 ] and NADPH-oxidase-mediated ROS production in microglia [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The TRPV1 agonist capsaicin was shown to prevent degeneration of dopaminergic neurons by inhibiting oxidative stress and neuroinflammation caused by activation of glia in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine model of PD [ 14 ]. Capsaicin was also shown to restore rotarod performance, as well as dopaminergic signaling, in the 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine model of PD [ 15 ]. It was further demonstrated that the neuroprotective effects of TRPV1 activation using capsaicin were mediated through endogenous ciliary neurotrophic factor and its receptors [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, these peptides interacted with free radicals, which may be one of the reasons for the reduced ROS levels. On the other hand, it is known that ion channels such as Kv and TRP and cell receptors such as P2X7 are actively involved in the regulation of neuronal processes, including inflammation, and are considered potential therapeutic targets for PD [61][62][63]. Recently, we showed that Kunitz-type peptides, namely HCRG1 and HCRG2, which are blockers of Kv channels, maintained ROS production in 6-OHDA-treated cells at the reference level [50].…”
Section: Discussionmentioning
confidence: 99%